Ocena realizacji programów rewitalizacji w dużych miastach na przykładzie miasta stołecznego Warszawy - Górniak, Remigiusz (Evaluation of Revitalization Programmes in Major Cities in Poland on the Example of Warsaw, 2008)
The general aim of the paper is presenting the results of implementing and managing the revitalization programme in Warsaw between 2004 and 2007. The key aspect of the paper is presenting the I author's critical conclusions concerning the results of implementing the revitalization programme in I Warsaw. The author presents the proposal of the direction that may be chosen by Warsaw authorities I in the field of programming and managing the revitalization processes. The paper is divided into three I parts. The first - defining and describing Warsaw revitalization programme, the second - explaining le term of revitalization, the last including the proposals for Polish cities for the future. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 393-401